COVID-19 and neuropsychiatric disorders: Common links and extended networks - Mohammad Azizur Rahman; Umme Habiba (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), a single-stranded RNA virus has been plaguing the world through spreading coronavirus disease 2019 (COVID-19). In addition to physiological complications, COVID-19 led neurological and psychological problems that have been documented since the outbreak of COVID-19 in December, 2019 in Wuhan, China. The present article demonstrates the neuropsychiatric complications associated with COVID-19. The current review would be of immense importance to those linked with COVID-19 mitigation, caregiving, health professionals, researchers, academicians as well as the COVID-19 sufferers.